Efficient computation of erfc(x) for large arguments. - Tellambura, C. (IEEE Transactions on communications)
A new, infinite series representation for the error function is developed. It is especially suitable for computing erfc(x) for large x. For instance, for any x⩾4, the error function can be evaluated with a relative error less than 10-10 by using only eight terms. Similarly, the error function can be evaluated with a relative error less than 8×10-7 for any x⩾2 using just six terms. An analytical bound is derived to show that the total error due to series truncation and undersampling rapidly decreases as x increases. Comparisons with two other series are provided